The impact of long-term provision costs on performance of trade in Serbia - Radojko Lukic (Economic and Environmental Studies (E&ES), 2017)
Long-term provision costs in trade are based on uncertain obligations in the future in relation to the goods sold. They mostly refer to warranty costs. Warranty costs are caused by repair and servicing of the sold products during the warranty period. They are function of the quality, usage and maintenance (storage) of sold product. In marketing sense, warranty costs are increasingly treated as an instrument of sales and customer satisfaction in terms of functionality and durability of the product. Regarding the above mentioned this paper primarily investigates the impact of the cost of long-term provisions - warranty costs on the performance of retailers, with special emphasis on Serbia. These theoretical, methodological and empirical findings should serve as a basis for retailers to efficiently manage warranty costs in order to achieve the target profit with maximum customer satisfaction.
Keywords: K12; L81; M31; M41; 330; quality; warranty; customer satisfaction; retail profit